Robotics - Ghosal, Ashitava (Oxford Unversity Press, 2006)
Robotics: Fundamental Concepts and Analysis introduces the science and engineering of robotics and covers mechanical manipulation and sensing. Comprehensive in its coverage, the book also covers some advanced topics which would be useful to both undergraduate and postgraduate students. Written in a lucid style, the text is student-friendly with a large number of examples and exercise problems